2020
DOI: 10.2196/19129
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Electronic Informed Consent in Biomedical Research and Stakeholders’ Perspectives: Systematic Review

Abstract: Background Informed consent is one of the key elements in biomedical research. The introduction of electronic informed consent can be a way to overcome many challenges related to paper-based informed consent; however, its novel opportunities remain largely unfulfilled due to several barriers. Objective We aimed to provide an overview of the ethical, legal, regulatory, and user interface perspectives of multiple stakeholder groups in order to assist resp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(81 citation statements)
references
References 58 publications
2
79
0
Order By: Relevance
“…Several interviewees highlighted that paper-based IC documents are difficult to understand due to the scientific and legal nature of the information and emphasized the importance to present information in an understandable and engaging manner to research participants. eIC can assist in this by making use of video, audio or graphics to convey information to participants, which is considered more effective than written text [ 19 ]. Nevertheless, a small number of interviewees were convinced that eIC would not influence the understanding of research participants compared to that of a paper-based IC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several interviewees highlighted that paper-based IC documents are difficult to understand due to the scientific and legal nature of the information and emphasized the importance to present information in an understandable and engaging manner to research participants. eIC can assist in this by making use of video, audio or graphics to convey information to participants, which is considered more effective than written text [ 19 ]. Nevertheless, a small number of interviewees were convinced that eIC would not influence the understanding of research participants compared to that of a paper-based IC.…”
Section: Discussionmentioning
confidence: 99%
“…Semi-structured interviews were conducted to seek the views and experiences of various stakeholder groups across Europe and the United Kingdom (UK) regarding (electronic) IC in clinical research. An interview guide was developed based upon a systematic literature review and the research aims [ 19 ]. This systematic literature review identified that more research regarding the personalization of an eIC platform and the long-term interaction with research participants was required.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[22] The e-consent includes multimedia components and provides numerous forms of interactions and customized options for the voluntary participation of a subject in a research study. [23] It is the process not only of obtaining a signature from the subject, but also of developing an interactive procedure that provides adequate information and increases participants' comprehension, by using multiple electronic systems and processes, such as text, graphs, audio, video, podcasts, websites, biological devices, and card readers, as shown in Figure 1. [24]…”
Section: Current Practice Of Informed Consentmentioning
confidence: 99%
“…Advances in technology have led to new opportunities to support the informed consent and assent process ( 19 ). Participatory methods have previously been proposed to involve patients in informed consent and assent design ( 20 ).…”
Section: Introductionmentioning
confidence: 99%